Self-starvation and the performance narrative in competitive sport - Papathomas, A.; Lavallee, D. (Psychology of Sport and Exercise, 2014)
Objectives: To provide an alternative to medical understanding of disordered eating in sport through an emphasis on personal perspectives. Design: This study draws on narrative theory to interpretively analyse the life of Holly, a female athlete who engages in severe self-starvation. Methods: More than 7 hours of life history data was gathered over a period of 8 months through unstructured interviews. Holly's story was analyzed through principles of narrative analysis, with attention afforded to both narrative content and structure. Results: Holly's life is characterized by a struggle to align her life experiences with a culturally specified "performance narrative" that lauds normative success. When neither her academic nor sporting endeavors are perceived to fulfil the achievement narrative, Holly is thrust into emotional turmoil and begins to conceive of self-starvation as a means to achieve. Conclusions: The performance narrative spans both academic and sporting cultural domains and it can play a role in athlete disordered eating.